What Governs Their Practices? A Study on Pre-service English Language Teachers Beliefs - Harendita, Monica Ella (LLT Journal: A Journal on Language and Language Teaching, 2017)
Pre-service teachers undergo an important phase, called teaching practice, before plunging in the real teaching. Thus, the experiences and what they do during the practice can be an interesting subject to study. In this light, this case study attempts to gain more understanding on the beliefs of some pre-service teachers with regard to learning and teaching, as well as to see the influence of their beliefs on their practices. The data were gathered from reflective journals and observations. The findings show that the participants held some beliefs in regard to teaching and learning. First, they believed that mutual respect should be maintained in classroom. Second, interrelated with the previous belief, for the participants, meaningful learning requires active participation. Third, the participants believed that learning should be motivating. Fourth, the participants held a belief that as a teacher they have flexible roles. Hopefully, the results of this study will be beneficial in informing teacher training education in order to prepare and assist their students better as future teachers.